2015
DOI: 10.5617/jmi.v2i2.993
|View full text |Cite
|
Sign up to set email alerts
|

Media Innovation in a Strange Place: Newspaper Differentiation on Åland

Abstract: This essay examines the cultural, economic and political contexts of the small but vibrant media market on the Åland islands as well as competition strategies deployed by managers at two local Finnish newspapers, Ålandstidningen and Nya Åland. The case study has a managerial framework and aims to address four questions: 1) what is the foundation for newspaper competition at Åland; 2) what institutional drivers determine the way these organisations operate; 3) how do managers experience competition and innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The death of print newspapers is yet to be seen in Åland, as they still have a strong base of paying readers. According to a study from 2015, around 14,000 households on the islands (70%) were paying to read a printed home-delivered paper in addition to subscribing to papers from Finland or Sweden (Lindén, 2015). Beyond these two newspapers, there is a public service company -Ålands Radio och TV (ÅRTV) founded in 1996 and financed with media fees -as well as a small private radio station, Steel FM.…”
Section: Structure Of the Media Marketmentioning
confidence: 99%
See 3 more Smart Citations
“…The death of print newspapers is yet to be seen in Åland, as they still have a strong base of paying readers. According to a study from 2015, around 14,000 households on the islands (70%) were paying to read a printed home-delivered paper in addition to subscribing to papers from Finland or Sweden (Lindén, 2015). Beyond these two newspapers, there is a public service company -Ålands Radio och TV (ÅRTV) founded in 1996 and financed with media fees -as well as a small private radio station, Steel FM.…”
Section: Structure Of the Media Marketmentioning
confidence: 99%
“…The two papers were fierce competitors for many years, and the underdog Nya Åland was about to overtake Ålandstidningen around 2007. Due to countermeasures, however, that did not happen (Lindén, 2015). Wiklöf considered merging the two, but acknowledges that competition between the two papers keeps the cost of advertisements down.…”
Section: åLand's Media Baronmentioning
confidence: 99%
See 2 more Smart Citations
“…Hansen et al reported that the newspaper in their study was also guided by the objective of anchoring the newspaper in a local identity. The editor even argued that local competition between newspapers was beneficial for the community, taking a position that is supported by various Lindén, 2015). The actors interviewed by Ijäs explicitly called for widening the reach and scope of their local newspaper to create an arena for debate and to promote Sámi culture and language.…”
Section: Lisbeth Morlandstø Innovation and Value Creation In Local Mmentioning
confidence: 99%